Esophageal stricture as a complication in post operative neonates with congenital esophageal atresia with tracheoesophageal fistula - Gupta, Tarun; Sweta Soni, Edamakanti; Onkareshwar Kavthekar, Saiprasad; Pralhad Bharati, Hemant; Patil, Santosh V.; Jadhav, Sudhakar (Journal of Neonatal Surgery, 2025)
Introduction: Esophageal Atresia (EA) with Tracheoesophageal fistula (TOF) is one of the commonest congenital anomalies encountered in the pediatric surgery with commonest postoperative complication as esophageal stricture (ES) and gastroesophageal reflux disease (GERD). The aim of this study was to identify factors associated with ES formation in EA with TOF during post operative period. Materials and Methods: This cross-sectional study was carried out in pediatrics surgery department. A total 30 neonates with EA with TOF who were diagnosed clinically and radiologically were included while pure atresia cases were excluded. The distance between upper and lower esophageal pouch was noted with ruler intraoperatively. Post operative soluble contrast dye study was done to detect leaks. If no was leak present then ratio of upper and lower esophageal pouch width (UPW: LPW) was measured. During follow up, ES and GERD were diagnosed clinically and radiologically. The data was analyzed using MS-Excel and SPSS software and p value < 0.5 was taken as significant. Results: The measurement of gap between upper & lower pouch was < 2cms and >2cms in 12(40%) and 18(60%) patients respectively. The ES was found in 9(30%), GERD in 1(3.3%) and both ES and GERD in 6(20%) patients. The ratio of UPW: LPW found to be more than 1.5, equal to 1.5 and less than 1.5 in 12,2 and 1 patient respectively with ES. Dilatation for ES was required in all those with UPW: LPW >1.5 which was statistically significant. The postoperative UPW:LPW ratio showed statistically significant correlation with the intraoperative gap between upper & lower pouch and anastomosis under tension. Conclusion: The ES had significant correlation with gap between upper & lower esophageal pouch more than 2 cm and anastomosis under tension. The ratio of UPW: LPW ≥1.5 needed dilatation for ES during follow up.